Study guides

☆☆

Q: What is G plus 5 equals g - 2?

Write your answer...

Submit

Still have questions?

Related questions

2 + g + 5 = g + 7

-2

gf(5) = g(f(5)) = g(5+1) since f(x) = x+1 and then g(6) = 3*6 - 2 = 18 - 2 = 16

g(x) = x + 3 Then f o g (x) = f(g(x)) = f(x + 3) = sqrt[(x+3) + 2] = sqrt(x + 5)

(g + 5)(g + 2)

g (x) = -3x+5 -3x= 5 x= -5/3

578392g

27-g = 2g+12 -3g = -15 g = 5

2.845 Kg

G(x) = log(2x) + 2, obviously!

2 H2 (g) + O2 (g) => 2 H2O (g) + 483.6 kJ

g(x) = 5. So whatever f(x) or f(-1) is, g of that is going to be 5.

It is an equation and the value of g is 2.

Addition is commutative.

It equals 5 g.

9g + 2 = 39g = 1g = 1/9 = 0.111111111

If "g" has a value then it would just be 5+(the value) Otherwise it would be 5+g G is a variable and therefor could be anything. You can not solve the equation further. The answer is simply 5+G. If you have a previous declaration that states that G=2, then 5+G would equal 7. In computer programming, equations like this are useful for repetitious calculations. For example, if G is the variable for a score in a game, we would start with G=0 and every time you get a point, the computer would calculate G=G+1. G, currently 0, plus 1, equals 1. If you get another point then G, currently 1, plus 1, equals 2. This can be repeated as needed without changing the equation.

No. It is a meaningless equation. You may have intended to say: 2 times the sum of x and g is equal to 2x plus 2g.

2g - 9 = -5 Therefore, 2g = 4 Therefore, g = 4/2 g = 2

Let f ( x ) = 3 x 5 and g ( x ) = 3 x 2 4 x

14

g equals 9If2g + 14 + 5g = 8g - 3 + 8then:7g + 14 = 8g + 5therefore7g - 8g = -14 + 5-g = -9g = 9.

G = 9, L = 1, O = 5, 6 or 7, P = 3, 4 or 5 and S = any unused digit...

The reaction will proceed to the right. 2 PCl3 will be consumed.

f(x) = 3x - 1 so f(-2) = 3*(-2) - 1 = -7 g(x) = - x so g(5) = - 5 Then f(-2) + g(5) = -7 - 5 = -12